Birgit Steinbügl: Deutsch-englische Kollokationen: Erfassung in zweisprachigen Wörterbüchern und Grenzen der korpusbasierten Analyse - Smit, Maria (Lexikos, 2007)
This study investigates the role of collocations in dictionary use, and the extent to which users' needs are taken into account in the process of dictionary writing. Steinbügl decided to concentrate on bilingual dictionaries, because this type of dictionary is relatively less well explored in metalexicographical literature. German-English examples are analysed and evaluated. Instead of selecting examples randomly, she uses a comparative corpus of 200 collocations she put together herself in accordance with scientific reasons explained in detail. She questions the selection of collocations from existing corpora for her purposes, because these corpora are based on competing collocational theories. In order to come to meaningful conclusions, she prefers to delineate her own research approach, also however investigating the structures of bilingual dictionaries and dictionary articles, as well as situations of dictionary use.